Analisa Kajian Perbandingan Koperasi Tradisional dan Koperasi Generasi Baru (New Generation Cooperative ) - R Taufik Hidayat; Prijambodo Prijambodo; Eddy Setyanto (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
New generation cooperative/NGC is  different with tradisional cooperative/TC. There is not NGC in Indonesia, but luxury developed in others countries. The basic reason deveope NGC are switching of consumer demand, from raw materual (example ; milk, cocoa, coffee, fish and other) to be industrial materual. Herein the concept of coopertiave, organization inovation, financial and others are different in the form of NGC. The objective of this article is a inpsiration for the reguation and cooperactive practices in Indonesia, from TC to NGC which have a different characteristic. Through analysis and syntesis some new generation coopereative refereces, be idenntift a concept, organization and management inovation, variable abd indicator between NGC with TC. Analysis and syntesis gives some result are : (a) bass reason of NGC are changing demand from raw material to be industrial material (b) there are 5 variable and 18 =indicator NGC(c) 7 models business cooperetaive (d) 3 contraints for developing NGC in Indonesia, are  : cooperative business scale, regulation support and public commitment.